UJI KUALITAS MINYAK GORENG KELAPA SAWIT MENGGUNAKAN METODE POLARISASI ALAMI DENGAN VARIASI LINTASAN OPTIS - Tommy Andri Palembangan; K Sofjan Firdausi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
According to Indonesian National Standards, the parameter of quality test of cooking oil consists of many aspects, accompanied by its various methods. Both the parameter and methods can't be done simultaneously. It takes a long time and quite expensive costs. Through this paper, proposed that the active optic parameter is an alternative parameter of cooking oil which experiencing some treatments.The tested sample is the palm oil, and its active optic character being measured by the change of polarization angle. The source of light which used in this experiment is a 100 watt fluorescent lamp. The sample condition divides by some parts, they are the new ones, old ones, after-used ones, and the expired ones. A place to put the sample called cuvette with the various optical track, started from 1 to 5 cm.The result of the experiment showed that the active optical properties changes linearly, depends on the length of optical path, however it's not linear with the concentration of oil. The parameter of the active optical properties is sufficient enough to show the quality of palm oil. Good quality of oil indicated by the swivel angle of the form is smaller than the oil with bad quality. This is in accordance with the validation result of Free Fatty Acid (FFA) test. In the future, this method can give accurate information and complete the parameter of quality standards which used nowadays, furthermore it's possible to applied to another form of oil. Keywords: Optical properties, the quality of palm oil, natural polarization.